2005
DOI: 10.1083/jcb.200407058
|View full text |Cite
|
Sign up to set email alerts
|

PI(4,5)P2-dependent microdomain assemblies capture microtubules to promote and control leading edge motility

Abstract: The lipid second messenger PI(4,5)P2 modulates actin dynamics, and its local accumulation at plasmalemmal microdomains (rafts) might mediate regulation of protrusive motility. However, how PI(4,5)P2-rich rafts regulate surface motility is not well understood. Here, we show that upon signals promoting cell surface motility, PI(4,5)P2 directs the assembly of dynamic raft-rich plasmalemmal patches, which promote and sustain protrusive motility. The accumulation of PI(4,5)P2 at rafts, together with Cdc42, promotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
119
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(130 citation statements)
references
References 38 publications
(52 reference statements)
8
119
1
2
Order By: Relevance
“…[21][22][23] In agreement with previous observations, 34 we observed that such probe almost exclusively localizes at the plasma membrane where it distributes in discrete microdomains partially colocalizing with lipid rafts (R.G., unpublished data, December 2005). The interaction of NK cells with target cells was followed by a rapid consumption of PIP2 in the area of cytolytic synapse, whereas in contact-free membrane areas or in noncytolytic interactions we did not observe major PIP2 variations, thus ruling out rapid membrane turnover as the process responsible for the localized loss of membrane-associated GFP-PH probe.…”
Section: Discussionsupporting
confidence: 80%
“…[21][22][23] In agreement with previous observations, 34 we observed that such probe almost exclusively localizes at the plasma membrane where it distributes in discrete microdomains partially colocalizing with lipid rafts (R.G., unpublished data, December 2005). The interaction of NK cells with target cells was followed by a rapid consumption of PIP2 in the area of cytolytic synapse, whereas in contact-free membrane areas or in noncytolytic interactions we did not observe major PIP2 variations, thus ruling out rapid membrane turnover as the process responsible for the localized loss of membrane-associated GFP-PH probe.…”
Section: Discussionsupporting
confidence: 80%
“…Using two chemically distinct dyes to uniformly stain the plasma membrane, we find that the puncta and patches are areas containing increased membrane surface area (folds and microvilli), consistent with two other reports (Colarusso and Spring, 2002;van Rheenen and Jalink, 2002) and are not sites of PIP 2 and/or lipid raft enrichment. Our observations, however, may be cell-type specific, because other groups using similar membrane dyes have concluded that PLC␦ 1 PH domain and mGAP43 accumulation in localized regions of the plasma membrane is not caused by locally increased membrane area but instead is attributed to rafts (Huang et al, 2004;Golub and Caroni, 2005). Recently, PKC␣ has been demonstrated to associate with detergent-insoluble fractions in a Ca 2ϩ -dependent manner attributed to raft binding (Rucci et al, 2005).…”
Section: Targeting Of Pkc␣ and The Isolated Pkc␣ C2 Domain To Puncta contrasting
confidence: 48%
“…In principle, the observed puncta and patches could represent large clusters of lipids and proteins containing high local densities of PIP 2 on the cytoplasmic surface of the plasma membrane, such as clusters of lipid rafts (Laux et al, 2000;Raucher et al, 2000;Tall et al, 2000;Brown et al, 2001;Kwik et al, 2003;Huang et al, 2004;Golub and Caroni, 2005). Alternatively, the puncta and patches could represent geometric features arising from high local densities of membrane surface area (Colarusso and Spring, 2002;van Rheenen and Jalink, 2002).…”
Section: Intracellular Targeting Of Native Pkc␣ and Its C2 Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, different pathways regulate cytoskeletal rearrangement and may compensate for the WASp defect. In addition to actin dynamics, Cdc42/WASp pathway regulates accumulation of raft patches at the cell surface in different cell lines [44]. These domains act as microtubule stabilizers through IQGAP1 association and promote sustained directional motility.…”
Section: Discussionmentioning
confidence: 99%